Переналаживаемая технологическая оснастка для выполнения сборочно-сварочных операций по установке, фиксации и сварке приварок - Обозин, Я. В.; Астафьева, А. А.; Шевченко, И. А. (ХНУРЕ, 2020)
This article contains a description of the adaptable technological equipment for performing assembly welding work on the installation of welds. Such equipment includes a universal assembly fixture for welding UAFW. Despite the increased efficiency with respect to manual installation, this device has several disadvantages. UAFW replaced the set of reassembled assembly and dismountable devices for installing welds RADDIW. This allowed us to further increase efficiency and profitability, while avoiding many disadvantages. These features of RADDIW allowed to use it as the basis for the automated i stallation of welding.
Keywords: технологическая оснастка; сборочно-сварочные операции; ПСРП-П